Autotransplantation of Ectopic Permanent Maxillary Incisors - Sarimah Mohd Mokhtar; Laila Abd Jalil; Nurhidayah Muhd Noor (Case Reports in Dentistry)
The report presents examples of successful cases of autotransplantation of ectopic teeth as donor in the treatment of clinically missing maxillary anterior teeth in young patients. The transplanted teeth were either severely ectopic, inverted, rotated or in an unfavourable position that they are commonly sacrificed as a result. Details of surgical technique as well as clinical and radiographic assessments were discussed.